An investigation of hardness and wear properties of AA 2014 after reinforcing TiB2 using GTA as a heat source. (2021) - Sivakumar, T.; Shanmugasundaram, A.; Mohapatra, Subinaya
Abstract: The aim of this work is to evaluate the role of Titanium Diboride (TiB2 ) in increasing the hardness and improving the wear behaviour of AA 2014 alloy. TiB2 were reinforced onto the surface of AA 2014 by using Gas Tungsten Arc (GTA) as the heat source. Based upon the number of trials, the optimum process parameters were estimated to be 150 A as welding current and 6 mm/s as torch speed. The properties like hardness and wear behaviour were declined up on the bead on plate welding. In order to regain the properties, the alloy was subjected to Post Weld Heat Treatment (PWHT). The hardness and wear behaviour of the TiB2 reinforced surface composite resulted in a positive trend, which proved the effectiveness of TiB2 particles. Characteristic analysis of AA 2014-TiB2 surface composite was done using Optical Microscopy (OM), Scanning Electron Microscopy (SEM), EDS analysis and X ray Diffraction (XRD).